Recombinant relaxin protects liver transplants from ischemia damage by hepatocyte glucocorticoid receptor: From bench‐to‐bedside. Issue 1 (10th May 2018) - Kageyama, Shoichi; Nakamura, Kojiro; Fujii, Takehiro; Ke, Bibo; Sosa, Rebecca A.; Reed, Elaine F.; Datta, Nakul; Zarrinpar, Ali; Busuttil, Ronald W.; Kupiec‐Weglinski, Jerzy W.
Abstract : Hepatic ischemia‐reperfusion injury (IRI) represents a major risk factor of early graft dysfunction and acute/chronic rejection as well as a key obstacle to expanding the donor pool in orthotopic liver transplantation (OLT). Although glucocorticoid receptor (GR) signaling may enhance cytoprotective programs, clinical use of glucocorticoid is limited because of adverse effects, whereas clinical relevance of GR‐facilitated cytoprotection in OLT remains unknown. We aimed to evaluate the significance of hepatic GR in clinical OLT and verify the impact of recombinant human relaxin (rhRLX), which may function as a GR agonist in a tissue/disease‐specific manner. Fifty‐one OLT patients were recruited under an institutional research board (IRB) protocol. Liver biopsies were collected after cold storage (presurgery) and 2 hours postreperfusion (before abdominal closure), followed by western blotting–assisted hepatic analyses. Forty‐three percent of OLTs failed to increase GR perioperatively under surgical stress. Post‐/pre‐GR ratios at postoperative day 1 correlated negatively with serum aspartate aminotransferase (AST)/cleaved caspase‐3 and positively with B‐cell lymphoma‐extra large (Bcl‐xL)/B‐cell lymphoma 2 (Bcl‐2) levels. In a murine OLT model with extended (18‐hour) cold storage, treatment with rhRLX ameliorated ischemia‐reperfusion (IR) damage and improved survival while up‐regulating hepatocyte GR and Bcl‐xL/Bcl‐2 expression in OLT. rhRLX‐induced GR suppressed hepatocyte high‐mobility group box 1 (HMGB1) translocation/release, accompanied by decreased Toll‐like receptor 4 (TLR4)/receptor for advanced glycation end products (RAGE), suppressed interleukin 1 beta (IL1β), chemokine (C‐C motif) ligand 2 (CCL2), C‐X‐C motif chemokine (CXCL)10, tumor necrosis factor alpha (TNFα), CXCL1, and CXCL2 levels, and attenuated neutrophil/macrophage accumulation in OLT. Inhibition of GR in hepatocyte culture and in OLT diminished rhRLX‐mediated cytoprotection. Conclusion : This translational study underscores the role of rhRLX‐GR signaling as a regulator of hepatocellular protection against IR stress in OLT. In the context of a recent phase III clinical trial demonstrating positive outcomes of rhRLX in patients with acute heart failure, studies on rhRLX for the management of IRI in OLT recipients are warranted. (Hepatology 2018;68:258‐273).